CXCL13 promotes thermogenesis in mice via recruitment of M2 macrophage and inhibition of inflammation in brown adipose tissue - Xie, Lijun; Wang, Huiying; Wu, Dan; Zhang, Feng; Chen, Wei; Ye, Yuqing; Hu, Fang (Frontiers in Immunology, 2023)
Brown adipose tissue (BAT) is mainly responsible for mammalian non-shivering thermogenesis and promotes energy expenditure. Meanwhile, similar to white adipose tissue (WAT), BAT also secretes a variety of adipokines to regulate metabolism through paracrine, autocrine, or endocrine ways. The chemokine C-X-C motif chemokine ligand-13 (CXCL13), a canonical B cell chemokine, functions in inflammation and tumor-related diseases. However, the role of CXCL13 in the adipose tissues is unclear. In this study, we discovered that the expression of CXCL13 in the stromal cells of brown adipose tissue significantly elevated under cold stimulation. Overexpression of CXCL13 in the BAT via local injection could increase energy expenditure and promote thermogenesis in obese mice. Mechanically, CXCL13 could promote thermogenesis via recruiting M2 macrophages in the BAT and, in the meantime, inhibiting pro-inflammatory factor TNFα level. This study revealed the novel role of adipose chemokine CXCL13 in the regulation of BAT activity and thermogenesis.